Vasohibins: new transglutaminase-like cysteine proteases possessing a non-canonical Cys-His-Ser catalytic triad - Sanchez-Pulido, Luis (Bioinformatics, 2016)
Summary: Vasohibin-1 and Vasohibin-2 regulate angiogenesis, tumour growth and metastasis. Their molecular functions, however, were previously unknown, in large part owing to their perceived lack of homology to proteins of known structure and function. To identify their functional amino acids and domains, their molecular activity and their evolutionary history, we undertook an in-depth analysis of Vasohibin sequences. We find that Vasohibin proteins are previously undetected members of the transglutaminase-like cysteine protease superfamily, and all possess a non-canonical Cys-His-Ser catalytic triad. We further propose a calcium-dependent activation mechanism for Vasohibin proteins. These findings can now be used to design constructs for protein structure determination and to develop enzyme inhibitors as angiogenic regulators to treat metastasis and tumour growth. Contact: luis.sanchezpulido@dpag.ox.ac.uk Supplementary information: Supplementary data are available at Bioinformatics online.